A homozygote novel L451W mutation in CECR1 gene causes deficiency of adenosine deaminase 2 in a pediatric patient representing with chronic lymphoproliferation and cytopenia. (18th August 2019) - Ekinci, Rabia Miray Kisla; Balcı, Sibel; Bisgin, Atil; Sasmaz, Ilgen; Leblebisatan, Goksel; Incecik, Faruk; Yilmaz, Mustafa
Abstract: Deficiency of Adenosine Deaminase 2 (DADA2) is a monogenic autoinflammatory disorder characterized by livedo reticularis, skin ulcers, subcutaneous rash, aphthous ulcers, and leukocytoclastic vasculitis, neurological signs such as early onset stroke and polyneuropathy. A minority of DADA2 patients suffer from severe cytopenia and lymphoproliferation. Herein, we report an adolescent patient, followed up as having a hematological disorder for many years, eventually diagnosed as having DADA2. In view of the presence of elevated acute phase reactants, hepatosplenomegaly, low IgM level, lymphopenia, anemia, and neutropenia, and a subtle neurological involvement we considered DADA2 diagnosis. The diagnosis was confirmed by identification of a novel L451W mutation in CECR1 gene. The patient has been successfully treated with etanercept, monthly intravenous immunoglobulin replacement, and low-dose methylprednisolone. In conclusion, although the absence of skin and neurological findings, low IgM levels, and persistent lymphopenia should lead the physicians to consider DADA2 in patients with particularly complicated hematological abnormalities.